Telezhkina O. A. Phraseology of poetic works of Dmitry Pavlychko as a constituent of phraseological system of Ukrainian language - Telezhkina O. A. (Philological Treatises, 2020)
The article deals with the question of phraseology functioning in the poetic works of D. Pavlychko. The author comes to conclusion that phraseological units used in poetry of D. Pavlychko are a part of phraseology of modern Ukrainian language, since the matter concerns both the poet’s use of existent PhU and active creation of new variants of phraseological combinations that can be used by all native speakers as they have generalized character and are freely perceived out of the text where they functioned as figurative expressive units.